1999
DOI: 10.1002/(sici)1097-0231(19990430)13:8<737::aid-rcm552>3.3.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry of canola, castor and olive oils

Abstract: A fast-drying sample preparation method, using a-cyano-4-hydroxycinnamic acid as a matrix in an acetonitrile/tetrahydrofuran solvent system, has been used to obtain the matrix-assisted laser desorption/ ionization (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Spectra for castor oil show an m/z peak at 955.77 as the dominating signal. This corresponds to the molecular weight of triricinolein . A similar peak is seen in MCO spectra at a molecular weight of 956.98.…”
Section: Resultssupporting
confidence: 63%
“…Spectra for castor oil show an m/z peak at 955.77 as the dominating signal. This corresponds to the molecular weight of triricinolein . A similar peak is seen in MCO spectra at a molecular weight of 956.98.…”
Section: Resultssupporting
confidence: 63%
“…The MALDI‐TOF spectra in Figure (a) confirm the grafting of thiols with the occurrence of peaks at 957.10, 1192.61, and 1280.40 for CO, COM, and COT, respectively. The MALDI‐TOF spectrum of CO indicated that the CO used comprised three ricinoleins . The molecular weight differences of COM and COT to CO were 235.51 and 323.3, which are equivalent to the molar mass of three mercaptoethanol (78.13 g mol −1 ) and three thioglycerol (108.16 g mol −1 ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…TAG analysis has been demonstrated with MALDI using either α-cyano-4hydroxycinnamic acid or 2,5-dihydrobenzoic acid (DHB). 8,9 Further research has shown that the addition of sodium salts such as sodium chloride (NaCl) increases sensitivity for the analysis of TAGs when using DHB as a matrix. 10,11 It was also observed that TAGs are prone to in-source fragmentation and that the addition of a strong alkaline such as sodium hydroxide (NaOH) reduces this phenomenon and thus increases signal.…”
mentioning
confidence: 99%